ON-LINE POLITICS AND VOTING: OVERCOMING THE DEMOCRATIC DEFICIT - Pendarovski, Stevo; Pachovski, Veno; Andonov, Marko; Mihajloski, Zoran; Cavdar, Kimo (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The advance of digital technology in the field of politics in the last 20 years has raised the expectations about enhancing the potentials of the long dominant model of representative democracy. The need to reinvigorate the overall political process was talked about since the first signs of decline in the civic engagement in the second half of the past century. In the meantime, technological gadgets, and, especially the great versatility of Internet applicability have indeed contributed for better communication between the political elites and their people and for sharing the information on the unprecedented level. Yet, the key challenge still seems barely touched: how to provide meaningful participation of the politically awakened individuals in the decision-making processes within the states. In the article we offer a brief survey of the European and USA achievements in the field of e-voting and Internet-voting in order to show how the political, technical and security concerns are still prevailing in the debates thus undermining the trust in the new modes of casting the votes. Also, we present the results of the survey done with 120 students in the Republic of Macedonia and their considerations about the eventual Internet voting in the country. Applying the descriptive and analytical methods we would argue that the immense possibilities for using Internet in politics are far from being exploited, so the initial miscalculation and failures should not discourage the communities from observing new pathways for improving the unavoidable digital component of democracy.